Grušovnik, Tomaž, Reingard Spannring, and Karen Lykke Syse, eds. Environmental and Animal Abuse Denial: Averting Our Gaze. Lanham, MD: Lexington Books, 2021 - Protopapadaki, Vicky (Conatus - Journal of Philosophy, 2024)
Environmental and Animal Abuse Denial: Averting Our Gaze edited by Tomaž Grušovnik, Reingard Spannring, and Karen Lykke Syse, stands as a groundbreaking work that delves into the intricate phenomenon of denialism, a critical barrier in addressing ecological crises and advancing animal rights. Through its compelling interdisciplinary lens, the book dissects the psychological, sociocultural, and political underpinnings of denial, challenging entrenched anthropocentric views. This review provides a critical analysis of the book and highlights its pivotal role in bridging theoretical ethics with real-world environmental and animal welfare challenges. The editors’ adept selection of contributions guides readers through a thought-provoking journey in denialism, encompassing personal introspection, societal critique, and a scrutinizing look at economic, political, and legal frameworks. Despite its primarily Western-centric perspective, the book is essential in advocating for a broader, more inclusive global dialogue in future research. The book emerges not just as an academic text but as an urgent call to action, resonating with scholars, policymakers, and activists. In essence, this work emphasizes the necessity for a transformative shift in how we perceive and interact with the natural world and its non-human inhabitants.